2016
DOI: 10.4034/pboci.2016.161.31
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Assessment and Cleaning Capacity of a Reciprocating System in Root Canals of Deciduous Teeth

Abstract: Objective: To assess root canal morphological results and cleaning capacity in deciduous teeth instrumented with a reciprocating system. Material and Methods: 15 deciduous molars and a total of 24 canals were selected for the study. Nine teeth (13 canals) were selected at random for microbiological analysis and 6 teeth (11 canals) were used for tomographic analysis of morphology. The roots used for the microbiological assessment were contaminated with standard strains of Enterococcus faecalis. All roots were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…In a previous study [10], the authors used the small 21:06 CRT file of 21 mm in length, of the WaveOne system and it was observed that it was effective for disinfecting and modeling the root systems of primary molars [7,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study [10], the authors used the small 21:06 CRT file of 21 mm in length, of the WaveOne system and it was observed that it was effective for disinfecting and modeling the root systems of primary molars [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…The WaveOne system allows greater flow of irrigating solution by removing smaller amounts of dentin from the channel walls [6], thus reducing the extrusion of debris and reducing the risk of damaging or frustrating the instrument in irregular channels as presented the primary teeth [5][6][7]. This method has also been shown to be more effective in disinfecting the radial channels of deciduous molars [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative analysis was performed for five articles for instrumentation time and two articles for transportation due to a lack of data in the other articles. The reasons for exclusion [21][22][23][24] are presented in Table 1.…”
Section: Prisma: Preferred Reporting Items For Systematic Reviews And...mentioning
confidence: 99%
“…Burklein et al [21], Kishore et al [22] Studies done on permanent tooth Jeevanandan et al [23] Reciprocation motion used in hand files Pinheiro et al [24] No comparison/control group used…”
Section: Studies Reasons For Exclusionmentioning
confidence: 99%